Vasectomy Beyond the Taboo: A Cross-Disciplinary Analysis of Biology, Law, and Religion in Indonesia - Ummi Bariroh; Wahyu Nisawati Mafrukha; Syifara Chika; Anjani Putri Retnaninggalih; Elva Angie Calista (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2026)
Although vasectomy has been clinically proven to be safer and 30 times more effective than female sterilization, its prevalence among Indonesian Muslim men remains very low due to social stigma, religious ambiguity, and the gender-biased burden of contraception. This urgency prompted the present study to examine the reasons why Indonesian Muslim men choose vasectomy and how they overcome sociocultural barriers, focusing on four men from West Java, Jakarta, Bangka Belitung, and East Java. This study employed a descriptive qualitative method with a phenomenological approach to understand the personal experiences of men who underwent vasectomy. Data were collected through in-depth semi-structured interviews, then analyzed to uncover the meanings of their experiences, along with the practical and spiritual reasons behind their decisions. The findings reveal three main driving factors beyond vasectomy decision: maintaining family economic stability, ensuring children's psychosocial well-being, and protecting the wife's health from medical risks. Legally, a vasectomy aligns with constitutional rights and Ministry of Health Regulation No. 2 of 2025 on reproductive rights. Despite facing social stigma and gender pressures, the participants regarded vasectomy as a moral and responsible choice. The study further concludes that vasectomy can be understood as a form of maá¹£laá¸¥ah within the framework of asy-SyÄá¹ibÄ«'s maqÄá¹£id asy-syarÄ«â€™ah, as it aligns with the objectives of protecting life (á¸¥ifáº“ an-nafs), lineage (á¸¥ifáº“ an-nasl), and wealth (á¸¥ifáº“ al-mÄl). In this context, vasectomy is not merely a medical procedure; it is equally a moral, social, and spiritual act of male responsibility that supports gender equity in family planning.